2009
DOI: 10.1002/eji.200838818
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of the P2X4 receptor in alveolar macrophages by phagocytosis and classical activation

Abstract: ATP-gated P2X 4 receptors (P2X 4 R) in macrophages and microglia have been implicated in neuropathic and inflammatory pain by currently unidentified mechanisms. P2X 4 R are found predominantly in intracellular lysosomal compartments but can be rapidly trafficked to the surface membrane by procedures that induce endolysosomal secretion. We studied total and surface membrane P2X 4 R protein expression by Western blot and biotinylation assays and functional expression by whole-cell patch clamp assays in human and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 40 publications
(67 reference statements)
6
63
2
Order By: Relevance
“…In our hands, to be effective, the activation of the plasma membrane receptors by the nucleotide had to be potentiated by ivermectin raising some doubts on their physiological role [37]. Stokes and Surprenant [24] have recently proposed a model to explain the contribution in vivo of the P2X 4 receptors to the physiology of macrophages. According to these authors, the activation of macrophages by a phagocytic stimulus promotes the translocation of P2X 4 receptors from the lysosomal compartment to the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our hands, to be effective, the activation of the plasma membrane receptors by the nucleotide had to be potentiated by ivermectin raising some doubts on their physiological role [37]. Stokes and Surprenant [24] have recently proposed a model to explain the contribution in vivo of the P2X 4 receptors to the physiology of macrophages. According to these authors, the activation of macrophages by a phagocytic stimulus promotes the translocation of P2X 4 receptors from the lysosomal compartment to the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
“…Brône and colleagues showed that ivermectin potentiated a current elicited by extracellular ATP in macrophages from WT mice but not from P2X 4 -KO mice [8]. Stokes and Surprenant [24] reported that ivermectin potentiated the current evoked by low concentrations of ATP in human alveolar macrophages. Our results are also fully consistent with recent results [25] who reported that ivermectin Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, P2X4 receptors form functional heteromers with P2X6 subunits (Lê et al, 1998a;Ormond et al, 2006) and undergo interactions with P2X7 receptors (Guo et al, 2007;Nicke, 2008;Alqallaf et al, 2009;Boumechache et al, 2009;Casas-Pruneda et al, 2009;MurrellLagnado, 2009). Progress has also been made in understanding the cell biology of P2X4 receptors, with evidence to suggest that they undergo endocytosis and traffic to lysosomes Royle et al, 2002;Toulmé et al, 2006;Qureshi et al, 2007;Stokes and Surprenant, 2009). Early studies showed that P2X4 receptors were widely expressed in the brain (Lê et al, 1998b;Rubio and Soto, 2001), whereas more recent studies show that they are also expressed in microglia and alveolar macrophages (Bowler et al, 2003;Tsuda et al, 2003;Raouf et al, 2007;Ulmann et al, 2008;Stokes and Surprenant, 2009).…”
Section: Surface Biotinylation Of P2x4 Receptorsmentioning
confidence: 99%
“…In addition to being present on the plasma membrane, some P2X receptors are also present within intracellular vesicular compartments (Ennion and Evans, 2001;Bobanovic et al, 2002;Toulmé et al, 2006;Fountain et al, 2007;Qureshi et al, 2007;Stokes and Surprenant, 2009). Seven P2X subunits comprise the P2X receptor family (P2X1-P2X7), with strong evidence to suggest that one type (P2X4) plays important roles in neuropathic pain (Tsuda et al, 2003;Coull et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…First cloned from rat brain [2,3], P2X4 subunits are expressed throughout the central nervous system, for example, in Purkinje cells [4], hippocampus [2] and dorsal horn of the spinal cord [5]. P2X4 is also widely expressed in non-neuronal tissues and can be found in the kidney, liver, pancreas [6], heart and lungs [7] oesteoclasts [8], and immune cells such as B lymphocytes [9] and macrophages [10]. In a great deal of these tissues and cells, the role of P2X4 receptors is not well understood.…”
Section: Introductionmentioning
confidence: 99%